2016
DOI: 10.1097/aln.0000000000001195
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation by Volatile Anesthetics

Abstract: Volatile general anesthetics continue to be an important part of clinical anesthesia worldwide. The impact of volatile anesthetics on the immune system has been investigated at both mechanistic and clinical levels, but previous studies have returned conflicting findings due to varied protocols, experimental environments, and subject species. While many of these studies have focused on the immunosuppressive effects of volatile anesthetics, compelling evidence also exists for immunoactivation. Depending on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
168
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(173 citation statements)
references
References 166 publications
2
168
0
3
Order By: Relevance
“…The immunomodulatory qualities of IAs are well reported in the literature. IAs decrease inflammation and attenuate lung injury by suppressing inflammatory responses (2,3). Mechanisms include modulation of alveolar macrophage r e s p o n s e s a n d G A B A A -r e c e p t o r m e d i a t e d a n t iinflammatory effects at the level of lung epithelial cells.…”
Section: Potential Pharmacophysiological Mechanisms Underlying the Prmentioning
confidence: 99%
“…The immunomodulatory qualities of IAs are well reported in the literature. IAs decrease inflammation and attenuate lung injury by suppressing inflammatory responses (2,3). Mechanisms include modulation of alveolar macrophage r e s p o n s e s a n d G A B A A -r e c e p t o r m e d i a t e d a n t iinflammatory effects at the level of lung epithelial cells.…”
Section: Potential Pharmacophysiological Mechanisms Underlying the Prmentioning
confidence: 99%
“…É tant donné que de fortes doses d'anesthésiques provoquent une dépression cardiovasculaire ainsi qu'une dégradation des réponses inflammatoires et immunitaires, 5,6 il n'est pas surprenant qu'une anesthésie profonde puisse entraîner une hypoperfusion tissulaire et, par la suite, un dysfonctionnement des organes. À cet égard, le débat fait rage quant à savoir si une anesthésie profonde peut causer une incidence accrue de delirium postopératoire et de trouble cognitif, 3,4,7,8 voire une augmentation de la récurrence de cancer ou de métastase.…”
unclassified
“…Given that large doses of anesthetics produce cardiovascular depression and impairment of inflammatory and immune responses, 5,6 it is not surprising that deep anesthesia could result in tissue hypoperfusion and subsequent organ dysfunction. In this regard, there is ongoing debate whether deep anesthesia can lead to an increased incidence of postoperative delirium and cognitive impairment, 3,4,7,8 and even increased cancer recurrence or metastasis.…”
mentioning
confidence: 99%
“…The identification and characterization of the immunosuppressive effects of inhalational agents has been challenging for researchers because of the many variables in the conditions of inhalational anesthesia administration and the different drugs to which patients are exposed. Figure 1 shows some of the direct immune modulations by volatile anesthetics [11]. In a large retrospective analysis, Schlagenhauff et al found a relationship between anesthesia and cancer survival rate: compared with the use of local anesthesia, general anesthesia was associated with a decreased survival rate for patients with primary melanoma excisions [3].…”
Section: Introductionmentioning
confidence: 99%